INNOVATIONS IN MEDICINE: FEATURES OF REGULATION AND PROSPECTS FOR THE DEVELOPMENT OF TELEMEDICINE - Baksheev, Andrei; Turchina, Zhanna; Sharova, Olga; Galaktionova, Marina; Chesnokova , Larisa; Rukavitsyna, Elena (Revista Inclusiones, 2020)
This paper deals with the organizational, legal, social, and ethical aspects of the use of remote forms of medical treatment and consulting in connection with the improvement of telecommunication technologies, in the event of an emergency or the threat of the spread of diseases that pose a danger to others, increasing the availability of medical care using the possibilities of telemedicine. The study aims to analyze the necessity and limits of legal regulation and ethical aspects of telemedicine. The authors have studied the regulations governing the remote forms of professional activities, as well as law enforcement practice and the opinions of specialists on this matter. The paper contains an analysis of practical situations related to the use of computer and telecommunication equipment, computers and peripheral devices; the authors have considered the legislative norms regulating liability for harm to health in the process of using telemedicine technologies and studied publications of Russian and foreign researchers on the formation and development of the market for remote medical services. Within the framework of the results of the study, the authors have described the main characteristics of telemedicine services and justified their point of view on the problems of their availability.